A multiplexed assay for quantifying immunomodulatory proteins supports correlative studies in immunotherapy clinical trials - Whiteaker, Jeffrey R.; Zhao, Lei; Schoenherr, Regine M.; Huang, Dongqing; Lundeen, Rachel A.; Voytovich, Ulianna; Kennedy, Jacob J.; Ivey, Richard G.; Lin, Chenwei; Murillo, Oscar D.; Lorentzen, Travis D.; Colantonio, Simona; et al. (Frontiers in Oncology, 2023)
Immunotherapy is an effective treatment for a subset of cancer patients and expanding the benefits of immunotherapy to all cancer patients will require predictive biomarkers of response and of immune-related adverse events (irAE). To support correlative studies in immunotherapy clinical trials, we are developing highly validated assays for quantifying immunomodulatory proteins in human biospecimens. Here, we developed a panel of novel monoclonal antibodies and incorporated them into a novel, multiplexed, immuno-multiple reaction monitoring mass spectrometry (MRM-MS)-based proteomic assay targeting 49 proteotypic peptides representing 43 immunomodulatory proteins. The multiplex assay was validated in human tissue and plasma matrices, where linearity of quantification was >3 orders of magnitude with median inter-day CVs of 8.7% (tissue) and 10.1% (plasma). Proof-of-principle demonstration of the assay was conducted in plasma samples collected in clinical trials from lymphoma patients receiving an immune checkpoint inhibitor. We provide the assays and novel monoclonal antibodies publicly available as a resource for the biomedical community.